Overexpression of lncRNA snaR is correlated with progression and predicts poor survival of laryngeal squamous cell carcinoma. Issue 5 (2nd December 2018) - Liang, Kun; Yang, Ying; Zha, Dingjun; Yue, Bo; Qiu, Jianhua; Zhang, Changming
Abstract: Long noncoding RNAs (lncRNA) snaR is a characterized oncogenic lncRNA in triple negative breast cancer and ovarian cancer, while its role in other human diseases is unknown. In the present study, we found that plasma levels of snaR were upregulated in patients with laryngeal squamous cell carcinoma (LSCC) than in healthy controls. Plasma levels of snaR increased with increase in AJCC stages. Follow‐up study showed that high plasma levels of snaR were correlated with poor overall survival. Plasma levels of snaR were positively correlated with transforming growth factor beta (TGF‐β1) in patients with LSCC but not in healthy controls. Overexpression of snaR resulted in upregulation of TGF‐β1 in cells of human LSCC cell lines, while exogenous TGF‐β1 treatment showed no significant effect on snaR expression. snaR overexpression and exogenous TGF‐β1 treatment promoted LSCC cell proliferation, migration, and invasion. In addition, TGF‐β inhibitor partially reduced the enhancing effects of snaR overexpression on LSCC cell proliferation, migration, and invasion. Therefore, overexpression of lncRNA snaR is correlated with progression and predicts poor survival of LSCC and the mechanism of its actions is likely related to TGF‐β1. Abstract : Long noncoding RNAs (lncRNA) snaR is a characterized oncogenic lncRNA in triple negative breast cancer and ovarian cancer, while its role in other human diseases is unknown. In the present study, we found that plasma levels of snaR were upregulated in patients with laryngeal squamous cell carcinoma (LSCC) than in healthy controls. Plasma levels of snaR increased with increase in AJCC stages. Follow‐up study showed that high plasma levels of snaR were correlated with poor overall survival. Plasma levels of snaR were positively correlated with transforming growth factor beta (TGF‐β1) in patients with LSCC but not in healthy controls. Overexpression of lncRNA snaR is correlated with progression and predicts poor survival of LSCC and the mechanism of its actions is likely related to TGF‐β1.